An in vitro study on the differentiated metabolic mechanism of chloroquine-resistant Plasmodium falciparum using high-resolution metabolomics. Issue 21 (2nd November 2021) - Na, Jinhyuk; Zhang, Jian; Choe, Young Lan; Lim, Chae Seung; Park, Youngja Hwang
ABSTRACT: Chloroquine (CQ) is an important drug used therapeutically for treatment of malaria. However, due to limited number of studies on metabolic targets of chloroquine (CQ), it is difficult to attribute mechanisms underlying resistance associated with usage of this drug. The present study aimed to investigate the metabolic signatures of CQ-resistant Plasmodium falciparum (PfDd2) compared to CQ-sensitive Plasmodium falciparum (Pf3D7). Both Pf3D7 and PfDd2 were treated with CQ at 200 nM for 48 hr; thereafter, the harvested red blood cells (RBCs) and media were subjected to microscopy and high-resolution metabolomics (HRM). Glutathione, γ-L-glutamyl-L-cysteine, spermidine, inosine monophosphate, alanine, and fructose-1, 6-bisphosphate were markedly altered in PfDd2 of RBC. In the media, cysteine, cysteic acid, spermidine, phenylacetaldehyde, and phenylacetic acid were significantly altered in PfDd2. These differential metabolic signatures related signaling pathways of PfDd2, such as oxidative stress pathway and glycolysis may provide evidence for understanding the resistance mechanism and pathogenesis of the CQ-resistant parasite.